The regulation of tetraspanin 8 gene expression—A potential new mechanism in the pathogenesis of bipolar disorder. Issue 7 (4th August 2017) - Schartner, Christoph; Scholz, Claus‐Jürgen; Weber, Heike; Post, Antonia; Freudenberg, Florian; Grünewald, Lena; Reif, Andreas
Abstract : In a previous study, we identified the single nucleotide polymorphism (SNP) rs4500567, located in the upstream region of tetraspanin 8 ( TSPAN8 ), to be associated with bipolar disorder (BD). Due to its proximal position, the SNP might have an impact on promoter activity, thus on TSPAN8 gene expression. We investigated the impact of rs4500567 on TSPAN8 expression in vitro with luciferase‐based promoter assays in human embryonic kidney (HEK293) and neuroblastoma cells (SH‐SY5Y), and its effect on expression of downstream associated genes by microarray‐based transcriptome analyses. Immunohistochemical localization studies on murine brain slices served to identify possible target regions of altered TSPAN8 expression in the brain. Promoter assays revealed decreased TSPAN8 expression in presence of the minor allele. Transcriptome analyses of TSPAN8 ‐knockdown cells, mirroring the effects of putatively reduced TSPAN8 expression in minor allele carriers, resulted in 231 differentially expressed genes with enrichments of relevant signaling pathways for psychiatric disorders and neuronal development. Finally, we demonstrate Tspan8 abundance in mouse cerebellum and hippocampus. These findings point to a role of TSPAN8 in neuronal function or development. Considering a rather protective effect of the minor allele of rs4500567, our findings reveal a possible novel mechanism that contributes to the development of BD.